A study of consumer preferences for e-retailer' attributes: An application of conjoint analysis - Bego\~na Peral Peral; Joaquina Rodríguez-Bobada Rey; Angel Francisco Villarejo Ramos (The International Journal of Management Science and Information Technology (IJMSIT), 2012)
The aim of this work is to determine and analyse consumer preferences regarding the profiles of an e-retailer's web page. Two types of products are examined, a pleasure trip and a laptop computer, to test whether there are differences in the individuals' preferences. There are two reasons for this choice: these two products are purchased the most over the Internet in Spain and the different motives for buying them hedonic-pleasurable and utilitarian. We conducted an initial study, from which we identified the principal attributes valued by the participants in the survey. These attributes were then used to design the profiles for the conjoint analysis. The variables that are most relevant to the shopping task are those which receive a higher response frequency. In both products, the attributes that are most valued by the participants are the virtual store's security and privacy policy. However, for a laptop computer, consumers also emphasize the importance of the provision of the technical details of the product and the fact that the supplier also has a physical store. We recommend that e-retailers' web pages need to clarify and facilitate access to the most relevant variables to the shopping task. Likewise, public institutions and e-retailers need to continue to work towards minimising non-buyers' rejection of online purchasing and their fears regarding security on the Web. Firms with both physical and online outlets have an important competitive advantage over pure-players, for certain products at least.
Keywords: 650; e-retailers; consumer behaviour; conjoint analysis